The Role of Trust on the Continuance Usage Intention of Indonesian Mobile Payment Application - Ansori, Ayu Diana; Nugroho, Sahid Susilo (Gadjah Mada International Journal of Business, 2024)
Mobile payment is a fascinating innovation, developed by the banking and fintech industries. It is growing very fast, shadowing the popularity of smartphones in Indonesia. However, the continuance usage intention of mobile payment still needs to be determined. Based on prior studies, this study investigates trust as an important factor in promoting the m-payment continuance usage intention.Furthermore, drawing upon the innovation diffusion theory, the study uses the model by Shao et al. (2019) to investigate the antecedents of trust: mobility, customization, security, and reputation, and analyzes the moderating effect of gender on the relationship between trust and its antecedents. It also examines the impact of trust on the perceived risk and continuance intention; and the perceived risk on the continuance intention. The postulated links between the variables were tested using a survey design. With 225 respondents who are e-wallet users in Indonesia, the study finds a positive effect of reputation, security, and customization on trust. Trust positively influences continuance intention, while the link between trust and perceived risk is negative. Compared to the previous study by Shao et al. (2019), the current study finds insignificant relationships between mobility and trust, as well as between the perceived risk and continuance intention. Furthermore, there was no moderating effect of gender on the relationship between trust and its antecedents.